(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
National monuments and religious interest: a difficult or impossible synthesis? ABSTRACT: The essay examines national monuments, a category of cultural heritage born in the years immediately following the unification with two different purposes: the desire to celebrate the new state and the decision to safeguard from the transfer some ecclesiastical establishments (monasteries and churches), whose monumentality was declared. The essay traces the history of national monuments trying to grasp the lines of cultural policy that have presided over the choices of the various governments. It then examines the evolution of the legislation of these cultural heritage, up to the 2017 law that defines for the first time the notion of national monument and the qualification of religious interest to grasp the possibility and the limits of its application to these cases. SOMMARIO: 1. Premessa. I monumenti nazionali: storia di un bene culturale - 2. Tra stabilimenti ecclesiastici e celebrazione dello stato unitario (1861-1946) - 3. La repubblica (1946-2020) - 4. Monumenti nazionali e interesse religioso - 4.a. Stabilimenti ecclesiastici ed esigenze di culto - 4.b. Monumenti nazionali e interesse religioso.